(untitled) (American Journal of Business Management, Economics and Banking, 2026)
In today’s hyper-competitive global landscape, SMEs represent the backbone of economies worldwide, contributing over 50% of employment and GDP in many emerging markets, yet they grapple with alarmingly high failure rates—often exceeding 70% within the first decade.